The features of administrative cases processing of the tax offenses in first instance courts - Сопілко, І. М.; Євсікова, О. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article explores the characteristic features of judicial proceedings arising out of tax relations inadministrative courts of first instance and also is proposed a classification of proceedings arising out of taxrelations.